Não adesão à terapêutica anti-hipertensiva na atenção primária à saúde : fatores associados e representações sociais das pessoas acometidas pela doença - Oliveira, José Valter Costa (2018)
Objective: To investigate the factors associated with non-adherence to therapy and to know the social representations of people affected by systemic arterial hypertension (SAH) on the treatment of the disease. Methods: This is an analytical, cross-sectional study with an association of quantitative and qualitative approaches. The quantitative sample included 472 users of Primary Health Care (PHC) in the city of Aracaju / SE. Data collection was carried out between August 2017 and March 2018, through the measurement of anthropometric measures, blood pressure and application of a structured form with questions of socioeconomic characterization, demographic, food consumption, health determinants, components of the therapy and self-assessments health and nutrition. The qualitative sample was a subsample of the quantitative made up of 32 social protagonists. The research technique adopted was the semistructured interview, analyzed by the Content Analysis method and interpreted by Theory of Social Representations. Results: The results showed a frequency of non adherence to the pharmacological treatment of 71.8% and a blood pressure control of 68% of the sample. Non-adherence to pharmacological therapy was associated (p <0.05) with adult users, higher sodium intake, excess weight, waist circumference (WC), lower number of prescription drugs, not following the prescription correctly, not attending return visits, use home remedies, and have negative health and food assessment. While the low level of education, higher sugar consumption, high blood pressure, risk of coronary artery disease and longer diagnosis were associated (p <0.05) with the lack of control of blood pressure. In qualitative findings, drug use emerged as the main component of social representation (RS) in antihypertensive therapy. The predominant lifestyle measures in the speeches were diet and physical activity. However, the statements showed resistance regarding the follow-up of these measures, due to issues inherent to the users themselves, or external to them. Conclusion: The work can contribute to the planning of actions aimed at a more effective participation of users in the treatment, granting them autonomy and the development of a holistic view of the health professional towards the user, favoring the effectiveness of the therapeutics (to be) recommended.